Factors influencing implementation of SAK EMKM on the preparation of MSME financial reports in Semarang City - Manan, Abdul; Rahmadhani, Sari (Indonesia Auditing Research Journal, 2024)
This research analyzes the factors that influence the application of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in preparing financial reports for MSMEs. The population in this study was 114 MSMEs in Semarang City, Central Java. The statistical analysis technique in this research uses multiple linear regression. The results of this research show that the socialization of SAK, human resource competence, understanding of accounting, and the size of MSME businesses have a significant influence on the application of SAK EMKM in preparing financial reports. Meanwhile, the perception variable of MSME actors does not have a significant effect on the implementation of SAK EMKN. The implications of the research results are important for MSME business actors in preparing good financial reports in accordance with SAK EMKM, which has a direct or indirect impact on business performance due to the presentation of accurate accounting information.